2014
DOI: 10.1074/jbc.m114.572040
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering a Molecular Mechanism of Neonatal Diabetes Mellitus by the Chemical Synthesis of a Protein Diastereomer, [d-AlaB8]Human Proinsulin

Abstract: Background:Human proinsulin provides a model for studies of toxic protein misfolding. Results: Folding efficiency of proinsulin is controlled by stereochemistry at position B8. Conclusion: The sign of a single angle can facilitate or impede disulfide pairing. Significance: A monogenic diabetes syndrome suggests that insulin has evolved to the edge of non-foldability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 55 publications
1
18
0
2
Order By: Relevance
“…As noted above, the folding pathway of proinsulin in the ER may be impacted adversely by an unfavorable ER folding environment. It has been recently shown that chemically synthetic proinsulin can robustly refold in vitro at pH 10; under these conditions the folding of some MIDY mutants can be accomplished successfully (Avital-Shmilovici et al, 2014). However, under condition of physiological pH within the ER, the folding environment seems to be less favorable for proinsulin folding.…”
Section: Proinsulin Misfolding In the Ermentioning
confidence: 99%
“…As noted above, the folding pathway of proinsulin in the ER may be impacted adversely by an unfavorable ER folding environment. It has been recently shown that chemically synthetic proinsulin can robustly refold in vitro at pH 10; under these conditions the folding of some MIDY mutants can be accomplished successfully (Avital-Shmilovici et al, 2014). However, under condition of physiological pH within the ER, the folding environment seems to be less favorable for proinsulin folding.…”
Section: Proinsulin Misfolding In the Ermentioning
confidence: 99%
“…Both teams utilized multi‐step conventional fragment condensation in constructing the linear precursor. More recently, this target was revisited by Kent and co‐workers who utilized their native ligation methodology to achieve an overall yield of 26%, based on the starting fragment .…”
Section: The Chemical Synthesis Of Proinsulin Igf‐i and Igf‐iimentioning
confidence: 99%
“…Chiral inversion even has been found to stabilize tertiary structural elements in certain cases 47 49 . In an interesting biomedically relevant case, D-substitution strategies applied to insulin have revealed that it undergoes conformational changes upon receptor binding 47 , an observation of relevance with respect to the molecular mechanisms of neonatal diabetes mellitus 50 . The chiral substitution strategy has also been previously applied to advantage in studying smaller peptides.…”
Section: Altering Backbone Conformational Landscapes With D-amino Acimentioning
confidence: 99%